Application of Concept Maps in computer engineering to assess meaningful learning - Fermín María González García; Jorge F. Veloz Ortiz; Iovanna A. Rodríguez Moreno; Luis E. Veloz Ortiz; Beatriz Guardían Soto; Antoni Ballester Valorí (Universitat Politècnica de València, 2012)
There are currently a very vast amount of work related to new models and styles of learning and mathematical instruction. In the case of the area covering the mathematical instruction - applied, there is less information success and work thereon. This occurs in the engineering degree in computer science is taught at the National Polytechnic Institute (IPN), Mexico. Due to its nature the theory of automata (TA) and compilers (Cs), present difficulties in understanding the concepts and applications by the student, so, we believe that there will be a propicius result in dynamism, understanding and meaningful learning in the long term that will provide solid elements for consequential subjects through the teaching strategy using mind maps developed by j. Novak, which are necessary and indispensable. The elaborate proposal is presented by Academy of professors, who taught the subject, implementation methodology, as well as exercises developed by students during their evolution, this to be carried out product of an invitation to success leads to an improvement to understand the two subjects, with passing results and resulting higher scores.